Factors that affect road accidents in Ecuador - Villa Maura, César Alfredo; Vargas Ulloa, Diana Evelyn; Merino Villa, Edgar Francisco (mktDESCUBRE; Vol 1 No 14 (2019): Fourteenth Edition (July - December), 2019)
In Ecuador, every day there are tragic events on the roads, the same ones that cause deaths and injuries, without considering material damages, economic losses and generating high costs in emergency and health care. It is proposed to differentiate the terms: "accident" as a casual event that cannot be prevented, focused on uncontrollable consequences; and, "sinister" as a causal, preventable event, focused on controllable prevention. The study is: a) Observational, the information is taken from the database of the National Transit Agency; and, reports provided by the ECU911, b) Retrospective, c) It is a cross-sectional study, all variables (accidents, accidents, deaths, injuries), d) Descriptive, the study is only carried out on the accident rate variable. Once the possible causes of the accidents have been determined, it is stated that 87.72% of the total is concentrated in only 11 causes, which, with an aggressive Road Safety program, could reduce deaths and injuries. This is related to qualitative research, in which the population indicates that the main causes are road infrastructure, user education and respect. It is everyone's responsibility to contribute to prevent traffic accidents and minimize the loss of life from this cause.